Developing Local Wisdom-Based Project Modules to Improve Pancasila Student Profiles - Rismawati Rismawati; Cut Mutia; Giovanni Oktavinanda; Refanja Rahmatillah (Yayasan Keluarga Guru Mandiri, 2025)
The purpose of this study is to examine the development process of a project module for Projek Penguatan Profil Pelajar Pancasila (P5) that integrates Aceh's local wisdom. The development focuses on three main aspects: 1) the tradition of storytelling; 2) a curated collection of engaging stories; and 3) the preservation and use of oral traditions. This research adopts a research and development approach, employing the 4-D model, which consists of four stages: defining, designing, developing, and disseminating. The study involved students and teachers from Sekolah Penggerak at phase B. In terms of data collection, the primary data consists of validation results of the project module by experts, while the secondary data was obtained from the trial phase. The data were analyzed using instruments measuring validity, practicality, and effectiveness to ensure the module met educational standards and addressed the intended competencies. Findings indicate that the developed module demonstrates a high level of practicality, enabling teachers to apply it easily in classroom and project-based learning contexts. Furthermore, the module proved effective in guiding teachers to facilitate activities that embody the values of Pancasila while promoting cultural appreciation among students.